Comparative Comparison of Antiseptic and Anti-Inflammatory Drugs in Destructive Changes of Dental Cartilaginous Tissue (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Periodontal diseases are one of the pressing problems of dentistry, leading to significant disorders of the dental system, the development of purulent-inflammatory diseases of the maxillofacial area and, in most cases, to infectious sensitization, chronic intoxication and changes in the immune status of the body